الخدمة العمومية المحلية في الجزائر بين التشريع و الواقع - دردوري, عبد الكريم (جامعة الوادي University of Eloued, 2017)
تعتبر الخدمات العمومية المحلية جميع الخدمات التي تتولى الإدارة المحلية (البلدية والولاية) توفيرها وتقديمها تلبية لحاجات أفراد الإقليم المحلي، بمقتضى الصلاحيات والاختصاصات المخولة من قبل المشرع، والذي منحها جميع الإختصاصات التي تهم الإقليم المحلي ، وهو ما يعطيها التكفل التام بجميع المسائل التي لها علاقة بالشأن المحلي، وعليه تتكفل البلدية بتوفير جميع الخدمات العمومية المحلية كخدمات الصحة والتعليم وتوفير المياه والتطهير، في حين يمتاز تدخل الولاية في تقديم الخدمة العمومية المحلية بالطابع المكمل لمهام ووظيفة البلدية، فهي تتدخل في حال تجاوز النشاط المتدخل فيه الإطار الإقليمي للبلديات أو لقدراتها المالية ، أما فيما يتعلق بواقع الخدمة العمومية المحلية، فإن مستواها يبقى متدني نظرا للتحديات التي تواجه الإدارة المحلية كضعف التمويل المحلي ونقص الخبرة لدى إطارات الإدارة المحلية سواء موظفين أو منتخبين، إضافة الى الرقابة المشددة التي تمارس عليها من قبل الوصاية وكذلك تأثير الفساد الإداري عليها وهي كلها عوامل ساهمت في تدني مستوى الخدمة العمومية المحلية، وهو ما يجبر الإدارة المحلية على توظيف وتفعيل آليات مختلفة تساهم في ترقية الخدمة العمومية المحلية، والوصول بها الى التميز. The public local services considred as all the services which control the local administration serving it , and providing all the individuals needs of the local region under the powers and specialities that is enacted by the authority and gives it all the affairs that concerns the local region ,which gives it the total care of all local issues, so the administration takes into consideration proving all those local services such as health, education, and water, mean while the state's interference in providing the local services in a way complete what the administration did, it interferences in case there was any excess in the work of administration or it financial local abilities , while conserning the local public services , the level is still so bad , because of the challenger's that the local administration is facing , like the poor funding, lack of experiences of the franes such as the stuff or elected, the strict oversight from the tutorship also the impact of administrative corruption these are all contributes in decrease of the level of the local public services that's what obliged the local administration on employing the different mechanism that contributes and getting wele The public local services.
قانون إداري
Keywords: الخدمة العمومية المحلية ، الإدارة المحلية ، التمويل المحلي; The public local services Local financing, The local administration